Enhancing Social Concern Through Community Partnership: The Effectiveness of NGO-Integrated Environmental Education - Prastiwi, Nadhya Indah; Siti Nurbayani K; Ade Budhi Salira (Journal of Innovation and Research in Primary Education, 2025)
Environmental education faces critical challenges in developing student environmental awareness and social concern, particularly regarding plastic waste management. This study examined the effectiveness of integrating the Campaign Reuse program from Masihan.id NGO as a Social Studies learning resource for enhancing social concern among seventh-grade students. A quasi-experimental design with non-equivalent control groups was employed at Mutiara 1 Bandung Junior High School during the 2024/2025 academic year. Participants included 47 seventh-grade students: 24 in the control group receiving conventional instruction and 23 in the experimental group experiencing Campaign Reuse program integration. Social concern was measured using a validated questionnaire (Cronbach's α = 0.878) administered pre- and post-intervention. Data analysis utilized independent-samples and paired-samples t-tests. The experimental group demonstrated significantly greater improvement in social concern scores (30.87-point increase) compared to the control group (8.54-point increase). Independent-samples t-test revealed statistically significant differences between groups (t = -8.077, p < .001), with a mean difference of 24.58 points favoring the experimental condition. Results support the effectiveness of community-based environmental education approaches integrated within formal curricula. The Campaign Reuse program successfully enhanced students' cognitive awareness, affective empathy, and conative behavioral intentions through experiential learning that combined theoretical knowledge with authentic environmental action. Findings validate school-community partnership models for character education development and support educational policies emphasizing experiential learning approaches within the Indonesian Merdeka Curriculum framework.